Cost-Effectiveness of Antithrombotic Agents for STEMI - M Fiqri Zulpadly; Jarir At Thobari; Lucia Kris Dinarti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
In Indonesia, the prevalence of Acute Coronary Syndrome (ACS) continues to rise annually and remains high. Aspirin and adenosine diphosphate receptor inhibitors are recommended as part of the dual antiplatelet therapy that is recommended by the standard guidelines for managing ACS. Ticagrelor, a new treatment option for ACS, has been made available during the current period of Indonesia's National Health Insurance. Ticagrelor is more effective, but it costs more. Objective: In patients with ST-Elevation Myocardial Infarction (STEMI), the goal of this study was to compare how much ticagrelor and clopidogrel cost when compared to one another with relative ratio (RR) analysis and 95% confidence interval (CI) with p